Implant of mesenchymal cells decreases acute cellular rejection in small bowel transplantation - Navarro Zorraquino, Marta (2020)
Objective: The objective of the study was to show adipose tissue-derived mesenchymal stem cells (AD-MSCs) immunomodulatory effects in small bowel transplantation (SBTx). Materials and methods: Forty Wistar Han rats (age: 10-12 weeks): were allogenic receptor rats and were allotted in 2 groups. Control group: rats undergoing orthopic SBTx ; AD-MSCs group: rats undergoing orthotopic SBTx plus AD-MSCs. Male Lewis rats were allogeneic small bowel donors. Rejection was confirmed by histological study of the explanted intestine, enterocyte apoptosis was determined in crypts and the lamina propria of the small bowel. Cytokine concentration levels (enzyme-linked immunosorbent assay) (interleukin [IL]-4, IL-10, IL-12, IL-17, IL-21, IL-23, tumor necrosis factor-alpha, and transforming growth factor [TGF]-b1) and cell percentages (flow cytometry) (CD3+ CD4+, CD8+, CD4+/25+, CD8+/25+, CD4+/25+/Foxp3+, and CD8+/25+/Foxp3+) were assessed in peripheral blood preoperatively and after death. Results: Treatment with AD-MSCs produced a significantly lower risk of rejection in the first 7 post-operative days (five rejection cases among 20 rats in the control group and only one case in the AD-MSCs group). Treg cells and TGFb1 levels showed a significant increase in the AD-MSCs group. Conclusions: The local implantation of AD-MSC in the anastomosis and the intestinal lumen can induce a regulatory immune response, by increasing the percentages of Treg cells and TGb-1 levels, leading to a lower risk of acute rejection by cell mediation, in the first 7 days of the intestinal transplant. We think that the implantation of AD-MSCs, in the anastomoses and in the lumen of the donor intestine, could give rise to a chimera of donor-recipient cells.